Friend recollections, and a collection of collaborations with Nadia - Monfils, Marie-H.; Lee, Hongjoo J.; Cofresí, Roberto U.; Gonzales, Rueben A. (Frontiers in Behavioral Neuroscience, 2022)
In this selective review article, we showcase our collaborations with our colleague, Nadia Chaudhri. Dr. Chaudhri was an esteemed colleague and researcher who contributed greatly to our understanding of Pavlovian alcohol conditioning. From 2014-2019, we collaborated with Nadia. Here, we reflect on our friendship, the work we did together, and the continued impact on the field.